Analisis Media Propaganda Herman-Chomsky dalam Ekonomi Politik Media pada Judi Online - Patrissia, Ressa Uli (Avant Garde, 2024)
In recent decades, online gambling has experienced strong growth and spread due to the intrinsic characteristics that make it very attractive to players (accessibility, anonymity, variety of games). The basic premise of the knowledge economy is prosperity, an increase in the general availability of economic values. This is a direct impact of people learning with new technology. According to contemporary policy writers, the only way to achieve prosperity is to increase the amount of knowledge available through more education and training; by reorienting education systems across countries towards profit-oriented outcomes; by commodifying communication between people; and, ultimately, by codifying, commodifying, and exploiting the entire experience of Society. This research aims to reveal the role of online gambling and the dominance of political economic elites in media propaganda to date in an interesting and relevant discourse on internet gambling from the perspective of Herman-Chomsky's propaganda media. This research uses a critical paradigm with a qualitative descriptive perspective. The results of this research are that the first filter from the media ownership side shows the benefits to be achieved by targeting a specific audience, related to financial increases, and the existence of an organizational hierarchy. The second filter covers the sponsorship side that influences online gambling advertising. The third filter on the source side looks at the dependability of online gambling organizations, the natural influence of player desires, and the influence of advertising and narrative. The fourth filter, namely flak, covers how to discipline online gambling media. The fifth filter concerns ideological predominance, the role of the internet industry to manipulate users through user-generated content.